A New Questionnaire for Estimating the Severity of Visual Height Intolerance and Acrophobia by a Metric Interval Scale - Huppert, Doreen; Grill, Eva; Brandt, Thomas (Frontiers in Neurology, 2017)
Aims To construct and validate a short scale for the assessment of the severity of visual height intolerance (vHI) and acrophobia. Methods The questionnaire was developed from two earlier representative epidemiological studies (n = 5,529). Items were applied in a telephone survey of a representative population-based sample. Results A total of 1,960 persons were included. The life-time prevalence of vHI was 32.7% (f: 36.1%; m: 28.4%); 12% of these persons fulfilled the psychiatric criteria of acrophobia. Rasch analysis of 11 items on severity, symptoms, and triggers resulted in an 8-item scale with good fit to the model. The score differentiated well between persons with and without acrophobia. The distribution of the scores on the metric scale of the questionnaires of those individuals with acrophobia is separate and distinct from that of susceptibles without acrophobia, although there is some overlap. Conclusion Our proposed short questionnaire (vHISS, see Table 1 and Supplementary Material) allows a continuous quantification of the severity of vHI within a metric interval scale from 0 to 13. The diagnosis of acrophobia can be established by including two additional questions.